Early Marriage and Domestic Violence: The Dilemma of Granting Marriage Dissolution Permission at the Jember Religious Court - Irwan Zamroni Ali; Kizza Magufuli Magufuli; Abdalla El Souwaim (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
The judge when examining a marriage dispensation case is in a dilemmatic position in considering the deterioration of the dispensation application being allowed and rejected. Granting a marriage dispensation application on the one hand can solve the problem. However, on the other hand, it can trigger domestic violence (KDRT). This research will analyze the practice of marriage dispensation at the Jember Religious Court and its implications for the potential for domestic violence. Therefore, this research is a field study located at the Jember Religious Court. The data collection method uses interview, observation, and documentation techniques. The data analysis process used the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results of the analysis found that: 1) In general, the practice of marriage dispensation in the Jember Religious Court has implemented Perma No. 5 of 2019 as an examination guideline. The strategy carried out by the Jember Religious Court to accelerate the examination process is to assign one of the judges who focuses on handling dispensation cases. In addition, the number of marriage dispensations at the Jember Religious Court is very high. Generally, people apply for dispensation, because they have been dating or engaged for a long time. 2) The practice of marriage dispensation at the Jember Religious Court has no impact on the number of divorces on the grounds of domestic violence. Generally, dispensation couples divorce for economic reasons, continuous disputes and arguments, and abandonment of one of the parties. From the data in the directory of Supreme Court decisions, especially in the Jember Religious Court, cases of divorce on the grounds of domestic violence are dominated by couples who marry at a sufficient age, and the marriage period has lasted a long time, even the marriage has produced offspring.